Patriotyzm w polityce – pojęcie tylko historyczne? - Kuglarz, Paweł (Horyzonty Wychowania, 2017)
The article takes up the issue of patriotism understood as thesocial-political attitude based on the principles of love and friendshiptowards the homeland, unity and solidarity with one’s ownnation, the sense of social bond and cultural community withcompatriots. The notion of patriotism has changed a lot throughthe years. The author depicts historical development of this conceptsince medieval times up to the present day. At present,patriotism essentially means work at the foundations, work forone’s own, but, at the same time, for the whole society.The issue of patriotism today requires new consideration,especially in the prospect of the processes of economic andcultural globalisation. If, in the past, patriotism was developing inthe perspective of the whole nation, or state, today, it rather relatesto small local communities, where people organise accordingto their private needs and interests, where tradition as wellas national and local culture are cultivated. The nation’s positionin the world can be measured by the value of culture and itspowers of radiation.Contemporary patriotism has to go hand in hand with convictionthat each homeland constitutes a part of a huge world homeland.Therefore, an attitude of openness to others is requiredas well as awareness that the increase of the ethical level of interpersonal elations takes place in the spiritual and cultural revivalof local traditions.